AKUNTANSI SUMBER DAYA MANUSIA: KAJIAN KRITIS ATAS PENGAKUAN PEMAIN SEPAK BOLA SEBAGAI ASET KLUB SEPAK BOLA DI INDONESIA - Baihaqi, Jadzil (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2014)
Title: [Human Resource Accounting: A Critical Study on Recognition of Football Player as Football Club Asset in Indonesia]The purpose of this study is to examine and criticize the theory of human resource accounting and IAS 38, specificly with regard to the football player recognition. This study also expands the accounting perspective to see the reality of a more holistic perspective, which is not only limited to the financial perspective. This study is a qualitative study by using the critical paradigm and a case study perspective. The result of this study is the form of new accounting concept, particularly the recognition of football players. Player recognition is not interpreted only from the economic perspective, but more important is the players have inherent factors, namely the spiritual factors, education/training, social/cultural, and environmental. These factors highly influence the player, so it does not suitable if the player is recognized as an asset and the monetary valuation is not always the best indicator.